Modern Rhinoplasty: Is There a Place for the Closed Approach? - Berghaus, Alexander (Facial Plastic Surgery, 2016)
Rhinoplasty is one of the most commonly performed cosmetic surgeries and, in many cases, an elective procedure. Therefore, it is crucial to assess the functional and aesthetic issues of the patient accurately and devise the proper surgical strategy most beneficial to the patient. Modern rhinoplasties can be approached by two distinct techniques: the open technique or the closed, endonasal technique. While most rhinosurgeons today prefer the open procedure due its superior access to the nasal scaffold and overview over the surgical field in particular, we highlight in this article techniques and benefits of endonasal rhinoplasty and critically discuss situations where such an approach yields superior results. Each rhinoplasty procedure, with its inherent strengths and weaknesses, has to be matched with a given nasal condition and the desired results to offer the maximum benefit to the patient. Therefore, each rhinosurgeon should be knowledgeable and trained in the endonasal technique. Open rhinosurgery is not always necessary and may even be disadvantageous in some cases.
Keywords: rhinoplasty; closed approach; open technique; endonasal technique